Réforme territoriale à l'italienne : d'une géographie des intérêts à une géographie de la rigueur - Dominique Rivière (EchoGéo)
In Italy, the debate upon about the territorial network - regional, local and provincial levels - was so far dominated by a general trend: the empowerment of the regions and of the local level, in a context of crisis of the North South solidarity. Nowadays a change is taking place due to the action of the State in a context of economic rigor imposed by the financial crisis. The territorial reform affects the emergence of a new «metropolitan cities» level, the prospect of a dismantling of the provincie and a tendancial shrinking of the regional level.